'Early identification of struggling pre-clerkship learners using formative clinical skills OSCEs: an assessment for learning program.'. Issue 1 (31st December 2022) - Rosenberg, Ilene; Thomas, Listy; Ceccolini, Gabbriel; Feinn, Richard
ABSTRACT: Multiple experts in clinical skills remediation recommend early identification to support struggling learners, but there is minimal documentation on implementation of these programs. We share one school's outcomes-based research utilizing the formative assessment for learning model to early-identify pre-clerkship students struggling with clinical skills using formative OSCEs (F-OSCE). Student scores were monitored over longitudinal F-OSCE experiences as part of a curricular innovation. Points towards early identification accumulated when a student's score fell below the 80% threshold for each section of an OSCE. Students who accumulated enough points were advised of the need for intervention, and coaching was recommended. Students were surveyed about their experiences with the program. The objective was to explore whether this early identification program and coaching intervention had a positive impact on subsequent OSCE performance. Of 184 students in 2 cohorts who completed F-OSCEs, 38 (20.7%) were flagged for early identification. Of these, 17 (44.7%) sought additional help by voluntarily participating in the coaching program. Students who participated in extra clinical skills coaching demonstrated statistically significant improvements in performance on subsequent FOSCEs, as did the early identified students who did not participate in extra coaching. The greatest impact of coaching intervention was noted in the physical examination domain. This program was effective in identifying students struggling with clinical skills on formative OSCEs. Early identified students demonstrated improvements in subsequent OSCE performance, with those who sought coaching faring slightly better. Development of robust early identification programs as formative assessments of clinical skills and follow-up coaching programs to guide skills development are important implications of this work. Monitoring short- and long-term results for students identified through this approach to see if improvement is sustained is planned.